The Muslim Council of Britain: Progressive Interlocutor or Redundant Gatekeeper? - Khan, Harun (Religions, 2020)
Since its inception in 1997, the Muslim Council of Britain (MCB) has evolved to become one of the most enduring British Muslim organisations. It is a representative body for over 500 member bodies (‘affiliates’) including mosques, schools and charities. During the course of the last two decades, it has been subject to external comment and sometimes critique by academics, media commentators, policy-makers, and others. This special issue of the journal Religions has provided a welcome opportunity for the current leadership of the MCB to write about the organisation from ‘within’, based on their long-standing time volunteering with it. This paper is based on an oral history methodology involving extended interviews with the oversight of a research director, supplemented by reference to existing academic and other sources. Therefore this paper is essentially a type of ‘edited transcript’ aggregated wholly from a series of first person interviews undertaken with the current senior elected leaders of MCB; reorganised for clarity and drafted out with added ‘prose’ allowing for it to be presented in essay form. The result is the first documented ‘insider’ perspective on the ways in which the MCB has tackled issues such as internal governance, the challenge of ‘representation’ in view of the diversity of British Muslim communities, changing relationships with government, and policy work. It becomes apparent through the paper that the MCB has matured into a constructively self-critical, pro-active, and more strategically professional body, that contributes to the flourishing of Muslim communities and the place of Islam in British society. The production of the paper is itself an indicator of the growing confidence and capacity of the MCB, and its ability to contribute positively to academic discourse and debate about Muslims in Britain.